From Agricultural to Household Pest:The Case of the Painted Bug Bagrada hilaris (Burmeister) (Heteroptera: Pentatomidae) in Chile - Faundez, Eduardo I. (My University, 2018)
Bagrada hilaris is an invasive stink bug present in Asia, Africa, Europe, North America, and recently found in Chile, South America. Painted bug is well known as an agricultural pest, attacking mostly Brassicaceae. First records of the painted bug B. hilaris invading homes are given from Chile, from the Metropolitan, and Valparaiso Regions, including mild and heavily infested homes. In addition, the first case ever of an adventitious bite in a human being by this species is provided and described. Additionally, first alleged cases of occupational allergy are also mentioned. The possible reasons of the occurrence of these invasions are commented and discussed. It is concluded that the invasions may be due because of the lack of food plant sources in nearby wild and agroecosystems; forcing the bugs to migrate to closely located cities. As a result, it is recommended to extend education and control programs from agricultural to urban residential areas.
Keywords: pentatominae; stink bug; invasive species; urban pest; bite